Respostas
respondido por:
5
temos: (4, 10, 14), ou seja, (a1,a2,a3); a15=?
An= a1 + ( n - 1 ).r
Para encontrarmos R, usaremos a fórmula R=a2-a1
R= 10-4
R=6
substituindo na 1° fórmula
An= a1 + (n - 1 ).r
A15 = 4 + (15-1).6
A15= 4 + 84
A15= 88
An= a1 + ( n - 1 ).r
Para encontrarmos R, usaremos a fórmula R=a2-a1
R= 10-4
R=6
substituindo na 1° fórmula
An= a1 + (n - 1 ).r
A15 = 4 + (15-1).6
A15= 4 + 84
A15= 88
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás